Orientation, Migration Routes and Flight Behaviour of Knots, Turnstones and Brant Geese Departing from Iceland in Spring - Alerstam, T.; Gundmundsson, G.A.; Jönsson, P.E.; Karlsson, J.; Lindström, Å. (ARCTIC, 1990)
Flight behaviour and orientation of 303 flocks (31,200 individuals) of migrating Knots and Turnstones and 77 flocks (3200 individuals) of Brant Geese departing from Iceland towards Nearctic breeding grounds were recorded during three spring seasons 1986-88. Flocks were tracked by telescope and optical range finder at three observation sites in western Iceland during the peak period of migratory departure, 25 May-1 June. Departing waders climbed steeply, often by circling and soaring flight, with an average climbing rate of 1.0 m/s, up to altitudes 600-2000 m asl. With unfavourable winds, the waders descended to fly low over the sea surface. Brant Geese usually travelled at lower altitudes, the majority below 100 m above the sea, and were more prone towards following coastlines than waders. The birds departed in flight formations, with mean flock sizes 100-200 individuals in the Knot, 13-70 individuals in the Turnstone and about 40 individuals in the Brant Goose flocks. Waders generally departed in the afternoon or evening, during rising or high tide. Significant differences in daily timing between seasons were associated with between-year differences in the tidal cycle. Within the season, departures took place earlier in relation to high tide as the season progressed. Brant Goose departures occurred in the morning and late evening. Mean orientation was close to 300 degrees in all three species, with angular deviation 21-26 degrees. It is concluded that the overwhelming majority of the birds are bound for breeding sites in northern Canada and northwest Greenland. The main flight route, as can be deduced on the basis of visual, radar and ringing data from Iceland, Greenland and Canada, falls in the 290-310 degrees rhumbline sector from Iceland, across the Greenland ice cap. There are simple celestial and magnetic orientation rules that would allow birds to orient from Iceland to northern Canada close to a great circle route, but not along the rhumbline route used by the Knots, Turnstones and Brant Geese.